2021
DOI: 10.1007/s11764-021-01151-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical judgment of the need for professional mental health care in patients with cancer: a qualitative study among oncologists and nurses

Abstract: Purpose In daily practice, oncologists and nurses frequently need to decide whether or not to refer a patient for professional mental health care. We explored the indicators oncologists and nurses use to judge the need for professional mental health care in patients with cancer. Methods In a qualitative study, oncologists (n = 8) and nurses (n = 6) were each asked to select patients who were or were not referred for professional mental health care (total n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Reconsidering life goals or finding alternative ways to achieve life goals may help to prevent emotional symptoms forming a tightly connected network of symptoms. The present conceptualization can also be used to improve adaptive functioning: oncologist and nurses have a critical role in supporting patients in this regard ( 12 , 72 ). Of course, these potential clinical applications require that empirical support is garnered for the present theory on emotions in patients with cancer, and in turn must themselves be empirically evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Reconsidering life goals or finding alternative ways to achieve life goals may help to prevent emotional symptoms forming a tightly connected network of symptoms. The present conceptualization can also be used to improve adaptive functioning: oncologist and nurses have a critical role in supporting patients in this regard ( 12 , 72 ). Of course, these potential clinical applications require that empirical support is garnered for the present theory on emotions in patients with cancer, and in turn must themselves be empirically evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…As this approach may have little or no beneficial effect on psychological distress [ 32 , 33 ], an alternative approach has been developed in which clinicians (physicians, nurses) provide emotional support and identify patients in need of professional mental health care (case finding) [ 15 ]. A qualitative study showed that some clinicians are indeed able to manage patients’ emotions using this approach [ 34 ]. These clinicians allowed patients time to adjust, while monitoring patients’ psychological well-being, especially if patients exhibit specific risk factors (“watchful waiting”).…”
Section: Brief Illustrationsmentioning
confidence: 99%
“…Risk and protective factors for emotional problems included personal, social, and disease- and treatment-related factors. Referral for professional mental health care was considered when specific indicators of emotional problems were noted, such as emotions with a negative impact on a patient’s daily life or treatment [ 34 ]. As it cannot be assumed that all clinicians are able to adequately manage patient emotions in this way, psychologists could provide additional training to help improve clinician’s performance [ 15 , 34 ].…”
Section: Brief Illustrationsmentioning
confidence: 99%
See 2 more Smart Citations